Direct state transfer in MLC based memristive ReRAM devices for ternary computing - Fey, Dietmar; Reuben, John Reuben (ECCTD 2020 - 24th IEEE European Conference on Circuit Theory and Design, 2020)
In this paper we present a new procedure for a direct state transfer in ReRAM based multi-level cell (MLC) memristors for future ternary data processing, i.e. the direct transitioning of one ternary MLC state to another state. According to the rules of a ternary stored-transfer-adder cell the content of two memristors storing three different resistance values are read out and processed by a sense amplifier to produce a new ternary state for two output memristors. In contrast to own older work the analogue-digital-converting of ternary MLC based memristors with subsequent digital processing is avoided what requires a comparatively high energy budget. The solution is based on an adapted version of an existing sense amplifier circuit realising an in-memory processing for a majority logic developed by our own. We present the new concept and simulation results characterising the functionality for the new memristive ternary MLC for a ReRAM technology from Innovations for High Performance Microelectronics (IHP).
CRIS-Team Scopus Importer:2020-12-04
Keywords: 1 Transistor-1 Resistor(1T1R); in-memory computing; majority logic; memristor; Non-Volatile Memory (NVM); von Neumann bottleneck